Partial inertion as basis of safety for pharmaceutical operations involving highly ignition sensitive powders and modeling combustion properties as a function of oxygen concentration. Issue 1 (5th August 2020) - Toth, Michael; Orella, Charles; Roth, Megan; Muzzio, Dan; Fisher, Elizabeth; Vickery, Thomas; Bachert, Don; Stone, Shane; Bader, Josh
Abstract: Pharmaceutical operations often require inertion or other suitable explosion protection systems when handling highly ignition sensitive materials. Regulating bodies typically require full inertion, which may be difficult and expensive to maintain. This work measured the influence of oxygen concentration on the values of the minimum ignition energy (MIE) as well as the explosion severity ( K st and P max ) for several of the most easily ignitable pharmaceutical powders. We found a significant increase in the MIE and decreases in the K st and P max by reducing the oxygen level to 12% to 15% v/v. The changes in MIE and explosion severity mean that partial inertion along with control of static should provide a satisfactory basis of safety for most unit operations handling these powders. We share these results to encourage others to examine the behavior of similar organic powders. Further, we have used the adiabatic flame temperature from combustion calculations to model the P max, limiting oxygen concentration, and MIE at reduced oxygen concentrations, and find very good agreement with the experimental values. This modeling can be a useful tool as a safe and economical alternative to testing when material is not available or for highly potent/toxic materials where testing is not preferred to avoid personnel exposure.